Targeting neuronal nitric oxide synthase by a cell penetrating peptide Tat-LK15/siRNA bioconjugate. (22nd May 2017) - Peng, Jie; Rao, Yun; Yang, Xue; Jia, Ji; Wu, Youping; Lu, Jianhua; Tao, Yuanxiang; Tu, Weifeng
Highlights: Tat-LK15 was used as a siRNA delivery to target nNOS expression. Tat-LK15/siRNA improved the stability of siRNA in serum. Tat-LK15/siRNA complex is efficient to knock-down nNOS expression in cells. Abstract: We developed a cell penetrating peptide (CPP) Tat-LK15, as a siRNA carrier to target nNOS. The feasibility, stability, efficiency and selectivity of this peptide-siRNA complex were evaluated in rat neuronal cells. We also compared the new method with conventional siRNA carrier Lipofectamine™. It was found that the CPP Tat-LK15 effectively and specifically delivered nNOS-siRNA into Rat retinal ganglia (RGC-5) cells and silenced the expression of nNOS. The CPP Tat-LK15 can conjugate with siRNA to form stable complex at a ratio of 2:1 (peptide/siRNA, w/w), which maintained stable in serum for as long as 4 h. The CPP Tat-LK15 was low-toxicity to cells, as the apoptosis rate of treat cells was not increased significantly when the used peptide lower than 10 μg/mL. Moreover, the cellular uptake of nNOS siRNA by Rat Neurons-dorsal spinal cord (RNdsc) cells was also significantly more than naked siRNA by RNdsc cells. The CPP Tat-LK15 was an efficient and stable, and non-cytotoxic siRNA delivery to neurons and effectively silenced the nNOS expression. The CPP Tat-LK15 mediated siRNA delivery was a potential tool to treat neuropathic diseases involving NO or nNOS neurotoxic cascades.